Protective microencapsulation of β-lapachone using porous glass membrane technique based on experimental optimisation. (18th August 2017) - Kim, Ki Hyun; Le, Tuan-Ho; Oh, Hee Kyung; Heo, Bora; Moon, Jeonghyun; Shin, Sangmun; Jeong, Seong Hoon
Abstract: Even though β-lapachone is a novel drug with pharmacological activity, it has limitations including instability under light conditions. The main purpose of the study was to enhance the stability of β-lapachone using the microencapsulation method. The Shirasu porous glass membrane was used to achieve uniform-sized microcapsules. The prepared microcapsules were evaluated to investigate how process parameters affect the encapsulation efficiency, photostability and particle size distribution. The experimental design was conducted to obtain optimal formulations. In addition, an operating space was drawn to identify the safer range of control factors. All control factors showed significant effects on the encapsulation efficiency and photostability. For example, when a large amount of polymers was used, encapsulation efficiency and photostability were improved. However, as the amount of polymers increased, large and polydisperse microcapsules were produced. The robust design method provided information to characterise significant factors, thereby allowing effective control of photostability and size of microcapsules.